2017
DOI: 10.1108/ilt-11-2015-0169
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mixed lubrication analysis of coated compression rings with worn cylinder profiles

Abstract: Purpose Compression rings are the main sources of frictional losses in internal combustion engines. The present paper aims to present a thermo-mixed hydrodynamic analysis for coated top compression rings. To understand the coating effects, the main tribological parameters are investigated into a ring-cylinder conjunction in a motorbike engine. Furthermore, flow simulations have been carried out on how different worn profiles on the cylinder inner liner affects friction, lubricant film and localized contact def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Reipert and Voigt [6] proposed that the magnitude of the thermal expansion is greater by far than the distortion caused by the clamping of cylinder head bolts. Zavos and Nikolakopoulos [3] have suggested that small thermal deformation will lead to less friction and wear in the cylinder liner. However, the thermal expansion is primarily a quasi-static deformation, with good radial continuity, which cannot cause obvious dynamic localised deformation on the liner surface, and therefore cannot cause direct impact on the friction and lubrication behaviour between piston rings and liner surface.…”
Section: ϕ R(ϕ)mentioning
confidence: 99%
See 3 more Smart Citations
“…Reipert and Voigt [6] proposed that the magnitude of the thermal expansion is greater by far than the distortion caused by the clamping of cylinder head bolts. Zavos and Nikolakopoulos [3] have suggested that small thermal deformation will lead to less friction and wear in the cylinder liner. However, the thermal expansion is primarily a quasi-static deformation, with good radial continuity, which cannot cause obvious dynamic localised deformation on the liner surface, and therefore cannot cause direct impact on the friction and lubrication behaviour between piston rings and liner surface.…”
Section: ϕ R(ϕ)mentioning
confidence: 99%
“…wherein η 0 is the lubricant viscosity at atmospheric pressure and ambient temperature 40 • C, p is the pressure, and Z and S are the dimensionless viscosity-pressure coefficient and viscosity-temperature coefficient, respectively, which can be calculated according to the literature [3,23]. T 0 is the ambient Energies 2017, 10, 2122 9 of 22 lubricant temperature, and the lubricant temperature T is calculated based on a series of heat flow balance equations [1,3,24].…”
Section: Average Reynolds Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of wear on tribological characteristics were also included in the study. Zavos et al [31] used Navier Stokes equation and experimental data from 2 Stroke engine. Surface irregularities are measured by using Coordinate Measuring machine (CMM).…”
Section: Top Ring Reversal Bore Wearmentioning
confidence: 99%